2020
DOI: 10.3390/soilsystems4010011
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Speciation in Long-Term Drained and Rewetted Peatlands of Northern Germany

Abstract: Previous studies, conducted at the inception of rewetting degraded peatlands, reported that rewetting increased phosphorus (P) mobilization but long-term effects of rewetting on the soil P status are unknown. The objectives of this study were to (i) characterize P in the surface and subsurface horizons of long-term drained and rewetted percolation mires, forest, and coastal peatlands and (ii) examine the influence of drainage and rewetting on P speciation and distributions using wet-chemical and advanced spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
(92 reference statements)
3
8
0
Order By: Relevance
“…The most remarkable changes in P forms due to marsh degradation was an increase in organic P concentration and proportion, and organic P became the predominant P form in surface soils in Zoige, which is consistent with the results of the Min River Estuary, China (Zhang et al, 2015). However, some studies have revealed that the concentration and proportion of organic P in wetland soils decreased because cultivation and drainage stimulated the transformation from organic P to inorganic P and increased organic P loss (Negassa et al, 2020;Schlichting et al, 2002;Wang et al, 2006). Negassa et al (2020) demonstrated that the proportion of organic P was higher in long-term rewetted peatlands than in drained peatlands.…”
Section: Marsh Degradation Influences the Transformation Of Soil Phos...supporting
confidence: 84%
See 2 more Smart Citations
“…The most remarkable changes in P forms due to marsh degradation was an increase in organic P concentration and proportion, and organic P became the predominant P form in surface soils in Zoige, which is consistent with the results of the Min River Estuary, China (Zhang et al, 2015). However, some studies have revealed that the concentration and proportion of organic P in wetland soils decreased because cultivation and drainage stimulated the transformation from organic P to inorganic P and increased organic P loss (Negassa et al, 2020;Schlichting et al, 2002;Wang et al, 2006). Negassa et al (2020) demonstrated that the proportion of organic P was higher in long-term rewetted peatlands than in drained peatlands.…”
Section: Marsh Degradation Influences the Transformation Of Soil Phos...supporting
confidence: 84%
“…The forms of P in soils generally exhibit evident variations owing to the differences and changes in the pedogenic environments of wetlands, such as parent material, hydrothermal, and vegetation conditions (Cheesman et al, 2010(Cheesman et al, , 2012Cui et al, 2019b;Negassa et al, 2020;Qu et al, 2021;Wang et al, 2016a). Presently, climate change, rodent harm, and human disturbances such as drainage, overgrazing, and aquaculture have led to the degradation of more than half of wetlands worldwide to some degree (Huisman et al, 2017;Nguyen et al, 2016;Ren et al, 2019;Zuquette et al, 2020), which has completely altered the conditions of hydrology, salinity, vegetation, and soil characteristics in some wetland ecosystems (Cheng et al, 2020;Li et al, 2022;Zeng et al, 2021;Zhao et al, 2017a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although peat formation is a slow process, rewetting a degraded area may be the most appropriate way to reduce CO2 (and other greenhouse gases) emissions from peat oxidation [87]. Rewetting can enable drained peatlands to become peat-forming ecosystems and turn them again into sinks for soil carbon and nutrients (including P, which-in the course of long-term rewetting-is not only locked in organic matter but also transformed from labile P to stable P fractions at the surface horizons of the different peatland types) [88,89]. The goal of peatland rewetting is to achieve a persistent and stable saturation of the peat body with water by raising the water table to the peat surface and reducing the water level fluctuations [90].…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Potential long-term influences of rewetting on phosphorus species were analyzed by Negassa et al [5] using traditional chemical and advanced spectroscopic methods. This indicated that rewetting could result in larger proportions of organic phosphorus and stable phosphorus fractions in the surface horizons of rewetted fens, compared to their degraded counterparts.…”
Section: Introductionmentioning
confidence: 99%